Early outcomes of treatment selections for infrarenal abdominal aortic aneurysms: The first five year experience of a single center - Bahadir Aytekin; Goktan Askin; Naim Boran Tumer; Hayrettin Levent Mavioglu; Seref Alp Kucuker; Ahmet Saritas; Hakki Zafer Iscan; Mehmet Ali Ozatik; Erol Sener (Turkish Journal of Vascular Surgery)
Aim: We examined the criteria governing patient selection in contemporary practice in cases of infrarenal abdominal aortic aneurysm (AAA) treated electively or urgently in our Cardiovascular Surgery Clinic (CVSC). Material and Methods: From January 2019 to January 2024, we retrospectively evaluated infrarenal AAA patients treated either electively or urgently with Open Surgical Repair (OSR) or standard Endovascular Aortic Repair (EVAR) at our CVSC. The primary endpoints are distribution of AAA patients by treatment modality, early morbidity and mortality. The secondary endpoints were intensive care unit (ICU) duration and length of hospital stay (LOS). Results: A total of 332 patients received EVAR (Group 1), including 296 elective cases, while 90 patients underwent OSR (Group 2), with 66 being elective. Early mortality rates were significantly lower in the EVAR group (1.3% for elective and 27.8% for emergent) compared to the OSR group (6.1% for elective and 54.2% for ruptured cases, p=0.001). Major postoperative complications occurred in 12.5% of elective EVAR patients and 39.4% of elective OSR patients (p=0.001), while in ruptured cases, the rates were 11.1% and 58.3%, respectively (p=0.001). Comparisons of ICU duration and LOS also favored EVAR (p=0.001). Conclusion: EVAR offers a survival benefit in the early period compared to OSR. The choice of treatment should be tailored to the patient's comorbidities, preferences, and the vascular surgeon's expertise. Advanced aortic centers with hybrid operating rooms (HOR) and specialized CVSCs should aim for optimized patient outcomes and cost-effectiveness in our country. [Turk J Vasc Surg 2024; 33(3.000): 120-6]